2012
DOI: 10.1525/jps.2012.xli.2.27
|View full text |Cite
|
Sign up to set email alerts
|

Digital Occupation: Gaza's High-Tech Enclosure

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of California Press and Institute for Palestine Studies are collaborating with JSTOR to digitize, preserve and extend access to Journal of Palestine Studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(25 citation statements)
references
References 0 publications
0
24
0
1
Order By: Relevance
“…Miller and Slater (2000: 5, 7), for instance, found through ethnographic work on Trinidad that uses of the Internet were always firmly rooted within ‘mundane social structures and relations’ and framed by users’ identities as Trinidadians, rather than producing a ‘self-enclosed cyberian apartness’. Contrary to earlier hopes of a borderless global community, the Internet was also revealed to be strongly marked by geopolitics, geoeconomics, and social constraints (Herrera, 2007: 74; Warf, 2010: 52; Witteborn, 2014; Zook et al, 2004: 162–164), by nationalism and territoriality (Aouragh, 2011; Diamandaki, 2003; Eriksen, 2007; Mills, 2002), and by the physicality of Internet infrastructure (Jungnickel, 2017; Gibson et al, 2012; Tawil-Souri, 2012; Zook, 2006: 59). Tawil-Souri (2012), for instance, has shown that in the Gaza Strip the capacity for the Internet to offer virtual mobility to a community whose spatial mobility is severely restricted is undercut by Israeli control over Palestinian IT infrastructure.…”
Section: Digital Place and Placelessnessmentioning
confidence: 76%
See 1 more Smart Citation
“…Miller and Slater (2000: 5, 7), for instance, found through ethnographic work on Trinidad that uses of the Internet were always firmly rooted within ‘mundane social structures and relations’ and framed by users’ identities as Trinidadians, rather than producing a ‘self-enclosed cyberian apartness’. Contrary to earlier hopes of a borderless global community, the Internet was also revealed to be strongly marked by geopolitics, geoeconomics, and social constraints (Herrera, 2007: 74; Warf, 2010: 52; Witteborn, 2014; Zook et al, 2004: 162–164), by nationalism and territoriality (Aouragh, 2011; Diamandaki, 2003; Eriksen, 2007; Mills, 2002), and by the physicality of Internet infrastructure (Jungnickel, 2017; Gibson et al, 2012; Tawil-Souri, 2012; Zook, 2006: 59). Tawil-Souri (2012), for instance, has shown that in the Gaza Strip the capacity for the Internet to offer virtual mobility to a community whose spatial mobility is severely restricted is undercut by Israeli control over Palestinian IT infrastructure.…”
Section: Digital Place and Placelessnessmentioning
confidence: 76%
“…Contrary to earlier hopes of a borderless global community, the Internet was also revealed to be strongly marked by geopolitics, geoeconomics, and social constraints (Herrera, 2007: 74; Warf, 2010: 52; Witteborn, 2014; Zook et al, 2004: 162–164), by nationalism and territoriality (Aouragh, 2011; Diamandaki, 2003; Eriksen, 2007; Mills, 2002), and by the physicality of Internet infrastructure (Jungnickel, 2017; Gibson et al, 2012; Tawil-Souri, 2012; Zook, 2006: 59). Tawil-Souri (2012), for instance, has shown that in the Gaza Strip the capacity for the Internet to offer virtual mobility to a community whose spatial mobility is severely restricted is undercut by Israeli control over Palestinian IT infrastructure. Yet, digital technology also created new opportunities for place-making, both in the physical world (Diamandaki, 2003; Goodspeed, 2017; Mills, 2002: 81) and in new virtual places (Boellstorff, 2008, 2013).…”
Section: Digital Place and Placelessnessmentioning
confidence: 76%
“…Aouragh’s work usefully points to the continuities between online and offline activities as the quest for a homeland continues. At the same time, reference must be made to the conditions of use in the Occupied Territories, a situation that has been described as digital occupation, because online access is essentially controlled by Israel, and it operates in a state of precariousness with constant shutdowns (Tawil-Souri, 2012).…”
Section: Twitter and Palestine: Setting The Contextmentioning
confidence: 99%
“…In other contexts, people contend with intermittent and precarious connections to online environments. Disconnection can also be forced, and at times is part of a violent politics of enclosure and occupation marked by intense state surveillance and control (Tawil-Souri, 2012). For instance, in August 2019, the right-wing BJP regime invoked sections of a British colonial-era law (Indian Telegraph Act of 1885) to suspend Internet services in the highly militarized north Indian state of Kashmir.…”
mentioning
confidence: 99%